Criminalization of Graft in Palestinian Legislation between Constitutional Legitimacy and Procedural Necessity : A Comparative Study - Al-Ashqar, Ahmad; Al-Atrash, Isam (Journal of Legal Sciences, 2022)
This study aimed to identify the extent of the constitutionality of proving the crime of graft regarding transferring the burden of proof to the accused and its violation of the presumption of innocence. The presumption of innocence, unlike the Kuwaiti legislator, who did not shift the burden of proof in the crimes of illegitimate gain, and that the proof of the crimes of illegitimate gain according to the Palestinian and Jordanian legislators are linked to two forms: actual exploitation and judgmental or presumed exploitation, while the Kuwaiti legislator has limited proof of illegitimate gain crimes in the form of The study recommended a set of recommendations for an amendment to the text of Article 3 of Decree Law No. 37 of 2018 regarding the amendment of Anti-Corruption Law No. 1 of 2005 that the burden of proof in graft crimes is entrusted to the authority of accusation in accordance with the rules the public.